Consensus recommendations for botulinum toxin injections in the spasticity management of children with cerebral palsy during COVID-19 outbreak - KARADAĞ SAYGI, NAİME EVRİM (TUBITAK SCIENTIFIC & TECHNICAL RESEARCH COUNCIL TURKEY, 2022)
Spasticity is the most common motor disturbance in cerebral palsy (CP). Lockdown in the COVID-19 outbreak has profoundly changed daily routines, and similarly caused the suspension of spasticity treatment plans. Besides, the delay in botulinum toxin (BoNT) injection, which is important in the management of focal spasticity, led to some problems in children. This consensus report includes BoNT injection recommendations in the management of spasticity during the COVID-19 pandemic in children with CP. In order to develop the consensus report, physical medicine and rehabilitation (PMR) specialists experienced in the field of pediatric rehabilitation and BoNT injections were invited by Pediatric Rehabilitation Association. Items were prepared and adapted to the Delphi technique by PMR specialists. Then they were asked to the physicians experienced in BoNT injections (PMR specialist, pediatric orthopedists, and pediatric neurologists) or COVID-19 (pediatric infectious disease, adult infectious disease). In conclusion, the experts agree that conservative management approaches for spasticity may be the initial steps before BoNT injections. BoNT injections can be administered to children with CP with appropriate indications and with necessary precautions during the pandemic.
Keywords: Botulinum toxin; cerebral palsy; COVID-19; pandemic; spasticity; ADVERSE EVENTS; GUIDANCE